Sulfur Mines Are Mined by Underground Smelting (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article deals with the extraction of sulfur minerals from underground by non-traditional (geotechnological) methods. In particular, this method is effective due to its uniqueness and simple technology. This method is widely used in the extraction of small or deep sulfur bodies from sulfur mining. Low melting temperature of sulfur mineral, i.e., ease of movement is the basis for this method. Sulfur minerals brought to a state of motion are brought to the surface with the help of wells.